Maximizing price stability in a monetary economy - Warren Mosler; Damiano Bruno Silipo (Levy Economics Institute of Bard College, 2016)
In this paper we analyze options for the European Central Bank (ECB) to achieve its single mandate of price stability. Viable options for price stability are described, analyzed, and tabulated with regard to both short- and long-term stability and volatility. We introduce an additional tool for promoting price stability and conclude that public purpose is best served by the selection of an alternative buffer stock policy that is directly managed by the ECB.
Keywords: E52; E58; 330; European Central Bank; Monetary Policy Tools and Price Stability; Buffer Stock Policy